2022
DOI: 10.29133/yyutbd.886006
|View full text |Cite
|
Sign up to set email alerts
|

Yazlık Buğdayda Verim ve Verim ile İlgili Genetik Parametrelerin F3 Açılan Populasyonlarında Tahmini

Abstract: The knowledge about genetic diversity of wheat genotypes is useful for the development of efficient cultivars adapted to diverse conditions. Various genetic parameters like broad-sense heritability, expected selection response, and correlation analysis were estimated among 12 F3 spring wheat populations derived from eight parents. The 20 wheat genotypes exhibited highly significant differences (P≤ 0.01) for all the studied traits. BT4N-11 × Zam-2004 revealed maximum spikes plant-1, while highest spikelets and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
0
0
Order By: Relevance
“…Agro-morphological characterization (Ghimire and Magar, 2017) and genotyping-by-sequencing (GBS) results in both showed that there is a high genetic diversity among Nepalese wheat landraces (Khadka et al, 2020). A crucial step in managing and utilizing the genetic diversity of any crop and for the development of better varieties is agro-morphological characterization (Manzano et al, 2001;Ali et al, 2022;Yüce et al, 2022). Smith and colleagues (1991) stated that significant traits of local landraces need to be assessed, characterized, and labeled.…”
Section: Introductionmentioning
confidence: 99%
“…Agro-morphological characterization (Ghimire and Magar, 2017) and genotyping-by-sequencing (GBS) results in both showed that there is a high genetic diversity among Nepalese wheat landraces (Khadka et al, 2020). A crucial step in managing and utilizing the genetic diversity of any crop and for the development of better varieties is agro-morphological characterization (Manzano et al, 2001;Ali et al, 2022;Yüce et al, 2022). Smith and colleagues (1991) stated that significant traits of local landraces need to be assessed, characterized, and labeled.…”
Section: Introductionmentioning
confidence: 99%